The nature of methadone diversion in England: a Merseyside case study - Duffy Paul; Baldwin Helen (BMC, 2012)
Abstract Background Methadone maintenance treatment (MMT) is a key element in treatment for opiate addiction; however concerns about the diversion of methadone remain. More current empirical data on methadone diversion are required. This research investigated the market for diverted methadone in Merseyside, UK, in order to provide a case study which can be transferred to other areas undertaking methadone maintenance treatment on a large scale. Methods Questionnaires were completed (in interview format) with 886 past year users of methadone recruited both in and out of prescribing agencies. Topic areas covered included current prescribing, obtaining and providing methadone, reasons for using illicit methadone and other drug use. Results Large proportions of participants had obtained illicit methadone for use in the past year with smaller proportions doing so in the past month. Proportions of participants buying and being given methadone were similar. Exchange of methadone primarily took place between friends and associates, with 'dealers' rarely involved. Gender, age, whether participant's methadone consumption was supervised and whether the aims of their treatment had been explained to them fully, influenced the extent to which participants were involved in diverting or using diverted methadone. Conclusion Methadone diversion is widespread although drug users generally do not make use of illicit methadone regularly (every month). The degree of altruism involved in the exchange of methadone does not negate the potential role of this action in overdose or the possibility of criminal justice action against individuals. Treatment agencies need to emphasise these risks whilst ensuring that treatment aims are effectively shared with clients to ensure adherence to treatment.